If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+4-6x=-7-x-3
We move all terms to the left:
5x+4-6x-(-7-x-3)=0
We add all the numbers together, and all the variables
5x-6x-(-1x-10)+4=0
We add all the numbers together, and all the variables
-1x-(-1x-10)+4=0
We get rid of parentheses
-1x+1x+10+4=0
We add all the numbers together, and all the variables
14!=0
There is no solution for this equation
| 53.75^z=44 | | 6x+21=52 | | 3x+2(—5)=35 | | -43.46=-8.2w | | 3x-9+6x+18=99 | | 3x-9=6x-18=99 | | -245=-35h | | -3+4x=19 | | 2x^2+700=0 | | 3x+9=6x-18=99 | | 3/8+x=2/3 | | 16x−4−8x=8x−10 | | 4x-25=2x-1 | | 2x+(2x+5)+x=145 | | -3x=x*(-3) | | 4-m/3=16 | | 10=a/3-4 | | 2/3m-1/3=5/24 | | 4^(3x+11)=7 | | n(n−2)(n+2)=n3−4n | | -4v+2=18 | | 1/2x-3=29 | | 5n+4=n+22 | | x/4+1=-9.24 | | 5-5p=20 | | 4-3b=31 | | 2X+x+4+x=x+20 | | -5-3m=13 | | 1/6x8=24 | | x+.8x=4275 | | -2n+4=6 | | 5x+27/15x=x |